2021
DOI: 10.3389/fnins.2021.749042
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate and Short-Term Effects of Transcutaneous Spinal Cord Stimulation and Peripheral Nerve Stimulation on Corticospinal Excitability

Abstract: Rehabilitative interventions involving electrical stimulation show promise for neuroplastic recovery in people living with Spinal Cord Injury (SCI). However, the understanding of how stimulation interacts with descending and spinal excitability remain unclear. In this study we compared the immediate and short-term (within a few minutes) effects of pairing Transcranial Magnetic Stimulation (TMS) with transcutaneous Spinal Cord stimulation (tSCS) and Peripheral Nerve Stimulation (PNS) on Corticospinal excitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…Further study is required for understanding the effects of multisite tSCS in individuals living with an SCI, as well as its effects on spasticity both within a session and after training. Interestingly, in neurologically intact study participants, modulated tSCS was unable to alter the excitability of either H-reflexes or MEPs when combined with either arm or leg cycling, regardless of whether single-site or multisite tSCS was applied [70,82]. This indicates that in neurologically intact individuals where interlimb coordination and the corticospinal tract are intact, the effects of arm or leg cycling on cervicolumbar coupling and corticospinal drive were not impacted significantly by the tSCS intensity used.…”
Section: Multiple Sites Of Tscs Converge To Facilitate Alterations In...mentioning
confidence: 90%
See 2 more Smart Citations
“…Further study is required for understanding the effects of multisite tSCS in individuals living with an SCI, as well as its effects on spasticity both within a session and after training. Interestingly, in neurologically intact study participants, modulated tSCS was unable to alter the excitability of either H-reflexes or MEPs when combined with either arm or leg cycling, regardless of whether single-site or multisite tSCS was applied [70,82]. This indicates that in neurologically intact individuals where interlimb coordination and the corticospinal tract are intact, the effects of arm or leg cycling on cervicolumbar coupling and corticospinal drive were not impacted significantly by the tSCS intensity used.…”
Section: Multiple Sites Of Tscs Converge To Facilitate Alterations In...mentioning
confidence: 90%
“…This is similar to our recent investigation, which found that modulated tSCS (33 Hz trains of 1 m long pulses with a 10 kHz carrier frequency) applied over the C3-4 and C6-7 spinous processes in neurologically intact individuals did not alter MEPs assessed in the forearm flexors [69]. Moreover, data from a paired associative stimulation (PAS) paradigm involving single pulses of transcranial magnetic stimulation (TMS) and unmodulated tSCS arriving at the same time at spinal motor neurons revealed increases in corticospinal excitability, but facilitation of MEPs following tSCS was less pronounced when tSCS pulses were filled with a carrier frequency [70]. These studies highlight the fact that in the presence of a carrier frequency, tSCS may be unable to facilitate MEPs.…”
Section: Mechanisms Of Tscs Recruitmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies have investigated tSCS modulation at both the cortical and spinal level [7][8][9][10][11][12][13]. Benavides et al, for example, investigated cortical modulation by comparing motor evoked potentials (MEPs) induced by transcranial magnetic stimulation (TMS) before and after 20 min of tSCS.…”
Section: Introductionmentioning
confidence: 99%
“…To deliver high currents with less discomfort, some groups deliver TSCS modulated with high frequencies ranging from 5 to 10 kHz. [18][19][20] While higher current intensities could be tolerated when the TSCS was modulated with a kHz frequency (TSCS-kHz), much higher currents were also required to reach PRR threshold (~180-200 mA for TSCS-kHz, compared with ~50 mA for TSCS 21,22 ), due to the TSCS-kHz waveform being active for half the duration of the TSCS waveform, and the apparently reduced neural recruitment efficiency with TSCS-kHz. 23 TSCS-kHz interventions are typically delivered in the range 60-120 mA 19,24 ; therefore, they are delivered at considerably subthreshold intensities with respect to the PRR threshold (~40%).…”
Section: Introductionmentioning
confidence: 99%